Paradoxic relations between basilar artery reconfiguration and superior cervical ganglia ischemia after bilateral common carotid artery ligation - Kılıç, Mustafa; Kılıç, Betül Aydın; Aydın, Mehmet Dumlu; Kanat, Ayhan; Yılmaz, İlhan; Eşeoğlu, Metehan; Gündoğdu, Betül (Elsevier, 2019)
Background: The relationship between superior cervical ganglia (SCG) ischemia due to bilateral common carotid artery ligation (BCCAL) and basilar artery (BA) reconfiguration was investigated. Methods: Twenty-three rabbits were randomly divided into 3 groups: group III rabbits underwent BCCAL (n = 13), group II rabbits were sham-operated controls (n = 5), and group I rabbits did not undergo surgery (n = 5). Degenerated neuron densities (DND) within the SCG were correlated with the BA vasodilatation index (VDI). Results: Mean live and DND in SCG of group I rabbits were 11.235 ± 982/?m3 and 11 ± 3/?m3, respectively, with a mean heart rate of 294 ± 21 beats/min. Mean SCG DND and heart rates were 213 ± 42/?m3 and 242 ± 17 beats/min for the sham group (group II) rabbits and 1743 ± 285/?m3 and 199 ± 19 beats/min for the study group (group III) rabbits, respectively. The BA VDI values in the sham group (group II) (1.32 ± 0.10) and the study group (group III) (0.976 ± 0.112) significantly differed from those in the control group (group I) (1.65 ± 0.12; P < 0.005) versus the sham group (group II) (P < 0.0001) versus the BCCAL applied group (group III) and between group II and group III (P < 0.005). Conclusions: A meaningful and paradoxic correlation was detected between the BA VDI values and degenerated neuron density of SCG after BCCAL. Although a low degenerated neuron density within SCG may provoke excessive sympathetic activity and prevent excessive BA dilatation with steno-occlusive carotid artery diseases, a high degenerated neuron density may cause dangerous vasodilatation of BA.
Keywords: Basilar Artery Vasodilatation; Common Carotid Artery Ligation; Degenerated Neuron Density; Superior Cervical Ganglion